Effect of O2/CO2 atmospheres on coal fragmentation. (1st May 2020) - Bareschino, P.; Urciuolo, M.; Scherer, V.; Chirone, R.; Senneca, O.
Abstract: Recently, a single particle pyrolysis-combustion fragmentation model has been developed (Senneca et al., 2013, 2017) [1, 2] to predict the propensity of coal particles to fragment under a wide range of heating conditions as a consequence of mechanical failure of the particle. Stress inside the particle arises from thermal shock, associated to particles' heat up, as well as from overpressure generated by volatiles release upon devolatilization. The model is now used to calculate the propensity of coal particles to undergo fragmentation in the early stages of oxy-combustion, with gaseous atmospheres of 5–30% O2 in CO2 in entrained flow and fluidized beds reactors. Accordingly particles size of 0.1–10 mm are assumed, temperatures of 1123 and 2073 K, heating rates of 100 and 10, 000 K/s. Results show that under entrained flow reactor conditions the particles break in the first 20–30 ms, producing a bimodal particle-size distribution. Under fluidized bed conditions, the particles undergo explosive fragmentation after 1–2 s, before pyrolysis is complete, generating broad particle size distribution. In both cases fragmentation occurs over short timescales compared to char combustion and gasification. Operative conditions where fragmentation occurs before or in parallel with char combustion or gasification are inferred by comparing on an Arrhenius plot the timescale of fragmentation and heterogeneous reactions for a larger array of operating conditions. The figure reveals that for high reaction temperatures, more reactive coals, larger particles size, gasification reactions can have an important role and maybe enhance porosity and percolative fragmentation.